2021
DOI: 10.5194/angeo-39-327-2021
|View full text |Cite
|
Sign up to set email alerts
|

Temperature decadal trends, and their relation to diurnal variations in the lower thermosphere, stratosphere, and mesosphere, based on measurements from SABER on TIMED

Abstract: Abstract. We have derived the behavior of decadal temperature trends over the 24 h of local time, based on zonal averages of SABER data, for the years 2012 to 2014, from 20 to 100 km, within 48∘ of the Equator. Similar results have not been available previously. We find that the temperature trends, based on zonal mean measurements at a fixed local time, can be different from those based on measurements made at a different fixed local time. The trends can vary significantly in local time, even from hour to hour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The negative temperature trends around −0.2 to −0.3 degrees per decade in the lower stratosphere are confirmed by [3] based on the MERRA2 and ERA5 reanalysis data for 1980-2019. The temperature changes in the higher parts of the middle atmosphere are discussed in more detail in many studies, e.g., [4,5], confirming the cooling of the stratosphere and mesosphere. Chemistry-climate models can also be used to analyze temperature trends, with the possibility of simulations of different radiative forcing and ozone-depleting substances emissions, e.g., [6,7].…”
Section: Introductionmentioning
confidence: 62%
“…The negative temperature trends around −0.2 to −0.3 degrees per decade in the lower stratosphere are confirmed by [3] based on the MERRA2 and ERA5 reanalysis data for 1980-2019. The temperature changes in the higher parts of the middle atmosphere are discussed in more detail in many studies, e.g., [4,5], confirming the cooling of the stratosphere and mesosphere. Chemistry-climate models can also be used to analyze temperature trends, with the possibility of simulations of different radiative forcing and ozone-depleting substances emissions, e.g., [6,7].…”
Section: Introductionmentioning
confidence: 62%
“…The general pattern is cooling, particularly in the mesosphere, but various observations are only mostly but not fully consistent, maybe partially due to insufficient length of the data series used; She et al ( 2019) claim that data sets longer than two solar cycles are necessary to obtain a reliable long-term trend. Huang and Mayr (2021) found that trends might significantly vary with local time and height in the whole height range of 30-110 km, but they studied data series that are only 13 years long. Also model simulations provide general cooling, even though the WACCM simulations by Qian et al (2019) indicate that the temperature trend becomes near-zero or even slightly positive in the summer upper mesosphere, likely due to dynamic effects (winds and atmospheric wave activity).…”
Section: Discussionmentioning
confidence: 99%
“…The most studied parameter was temperature. Huang and Mayr (2021) found that trends might significantly vary with local time and height in the whole height range of 30-110 km, but they studied data series that were only 13 years long. However, She et al ( 2019) claim that data sets longer than two solar cycles are necessary to obtain a re-liable long-term temperature trend.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied parameter was temperature. Huang and Mayr (2021) found that trends might significantly vary with local time and height in the whole height range of 30-110 km but they studied data series only 13 years long. However, She et al (2019) Meteor radar wind data from high/middle latitudes revealed no significant trend in diurnal tides and changes of semidiurnal tide, which differ according to altitude and latitude.…”
Section: Discussionmentioning
confidence: 99%
“…consistent, partially maybe due to insufficient length of data series used; She et al (2019) claim that data sets longer than two solar cycles are necessary to obtain reliable long-term trend. Huang and Mayr (2021) found that trends might significantly vary with local time and height in the whole height range of 30-110 km but they studied data series only 13 years long.…”
Section: Mesosphere and Lower Thermospherementioning
confidence: 99%